Elmer Kelton's The familiar stranger - Kelton, Steve; Bradshaw, John (Novelist) (Hewey Calloway novels, 2024)
"Elmer Kelton's Hewey Calloway, one of the best-loved cowboys in all of Western fiction, returns in this novel of his middling years, as he looks for work--but not too much work--in 1904 West Texas. Hewey Calloway had intending to pass straight through Durango, Colorado, en route to visit a friend several miles northeast of the city. He had left his home range about a year before, with a herd of young horses. It was supposed to be a relatively straightforward affair; deliver the horses, collect the payment, and return home with the money. Things got out of hand, however, and there he was in Durango a year later with plans to go north rather than south. Oh, well, he thought, he had always wanted to see new country. It isn't long before his travels lead him to a cabin on a rainy night. There he meets a young man, sick as a dog, who weakly tries to send him off. And for good reason: the man has smallpox, and soon enough, Hewey catches the deadly disease. The man cares for him in turn, and it's just as he is feeling better that the man disappears. The next morning a Pinkerton detective turns up with posse, looking for a wanted bank robber. As he travels north, Hewey seems to run in with both the young man who tended to him, as well as the detective. But something seems off about the Pinkerton detective, and Hewey keeps his mouth shut. When he reuinites with his friend Hanley, they do everything they can to get to the bottom of the mystery that threatens both theirs and this young man's life"--